The role of television in fostering national unity amongst multiethnic society of Malaysia (1963 - 1998) / Badariah Zakaria - Zakaria, Badariah (2013)
Unity - national unity to be precise - is always in the mind of the nation since the dawn of Merdeka when Malaysia (formerly Malaya) gained her independence from the British in 1957. The newly bom nation inherited a melange of various races, religions, cultures and ethnic backgrounds - predominantly Malays, Chinese and Indians; and a wide ethnic diversity from Sabah and Sarawak such as Kadazan, Iban, Bidayuh, Dayak, Melanau and Bajau. From that moment on, the entire diverse communities are expected to understand, accept, appreciate, respect, and enjoy each other’s culture and existence; as a result of which there is a desired state of ‘oneness’ - unity in diversity. This study explores the role of televisions, both public (first launched in 1963) and private (first launched in 1984) in fostering the spirit of national unity amongst the multifarious society in the critical period from 1963 to 1998 - a long span of 35 years - uncovering a rich historical tapestry of the broadcasting era. Through in-depth interviews, the researcher solicits the expert testimonies from seventeen (17) informants, who are highly experienced senior officials from the broadcasting industry (retired or still in service), based on a set of four (4) research questions in terms of: i) ownership, policies and regulations, ii) programming strategies, iii) socialisation and social networking, and iv) language utilisation. The data gathered from the informants were, in turn, examined and analysed by using constant comparative method of data analysis and peer validation. The data were then validated by applying the theoretical sampling process to arrive at the findings in the form of themes that really shape the answers to the research questions. The researcher is mindful and ensures the validity (both internal and external) and reliability of the findings by following the basic rules in qualitative research. Finally, the study reveals that indeed televisions have succeeded in contributing to these positive findings (i.e. fostering national unity) by observing the guidelines of the Federal Constitution and Broadcasting Act, adhering to the sets of government policies and regulations, guided by Broadcasting Code of Ethics, relying on the elements of Rukunegara and promoting the spirit of Muhibbah, to cite a few. The findings, judging by the number and variety of themes that have emerged; clearly infer that televisions (both public and private) have taken sustained serious efforts in fostering the spirit of national unity amongst the multi-ethnic society in the period of study from 1963 to 1998. The informants further opine that though television audience is inevitably segmented by the arrival of the private television (starting with TV3 in 1984 after a long broadcasting monopoly by RTM from 1963 to 1983), the degree of national unity remains ‘fairly strong’. The study is guided by two relevant theories, namely: a) Media Development Theory, and b) Agenda Setting Theory. At the conclusion of the study, the theories themselves are in turn further refined by ‘theoretical contributions’ and the research enriched with ‘practical contributions’.